Manajemen Sekolah Berbasis Pesantren Dalam Membentuk Karakter Peserta Didik - Saadah, Rifngatus; Asy’ari, Hasyim; Jemani, Abdurahman (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2022)
This article aims to find out how to build character in pesantren-based schools through intracurricular, extracurricular, and co-curricular activities. There is a plus value attached to this pesantren-based school because it maintains the distinctive culture of pesantren as an educational institution whose main orientation is to instill religious values ​​as forming the morality of the nation's children. This research is a type of qualitative research using a case study approach that is included in a descriptive research study. The location of this research is Islamic Junior High School Nashihuddin Bandar Lampung. Data were collected through participatory observation, structured interviews, and documentation. The results of this study can be concluded that: (1) character building in Islamic Junior High School Nashihuddin Bandar Lampung carried out thorough planning starting with the formulation of the vision, mission, and goals; (2) character building is integrated through intra-curricular, extra-curricular, co-curricular activities, such as flagship programs such as the English Club, Qiro 'Wal Hufadz and the Yellow Book Study; (3) Monitoring and evaluation of character building is carried out through (1) development of agreed character value indicators; (2) compiling assessment instruments; (3) summarize the results of indicator achievements; (4) perform analysis and evaluation; (5) follow up.